1994
DOI: 10.1016/s0006-3495(94)80575-2
|View full text |Cite
|
Sign up to set email alerts
|

Membrane solubilization by a hydrophobic polyelectrolyte: surface activity and membrane binding

Abstract: We have previously observed that the hydrophobic polyelectrolyte poly(2-ethylacrylic acid) solubilizes lipid membranes in a pH-dependent manner, and we have exploited this phenomenon to prepare lipid vesicles that release their contents in response to pH, light, or glucose (Thomas, J. L., and D. A. Tirrell. Acc. Chem. Res. 25:336-342, 1992). The physical basis for the interaction between poly(2-ethylacrylic acid) and lipid membranes has been explored using surface tensiometry and fluorimetry. Varying the polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 7 publications
7
62
0
Order By: Relevance
“…With increasing the concentration of the adsorbed PP75 to 5.8 μM, the virus-mimicking liposomes displayed a high level of relative hemolysis at 71.9 ± 3.1 % at pH 7.4. This is consistent with the report that a sufficiently high concentration of poly(α-ethylacrylic acid) may lead to complete membrane destabilization 45 . With acidification to pH ≤5.0, the PP75-coated, virusmimicking liposomes lost their hemolytic activity as a result of the formation of liposomal aggregates ( Figure 4A).…”
Section: Cell Membrane Destabilizationsupporting
confidence: 93%
“…With increasing the concentration of the adsorbed PP75 to 5.8 μM, the virus-mimicking liposomes displayed a high level of relative hemolysis at 71.9 ± 3.1 % at pH 7.4. This is consistent with the report that a sufficiently high concentration of poly(α-ethylacrylic acid) may lead to complete membrane destabilization 45 . With acidification to pH ≤5.0, the PP75-coated, virusmimicking liposomes lost their hemolytic activity as a result of the formation of liposomal aggregates ( Figure 4A).…”
Section: Cell Membrane Destabilizationsupporting
confidence: 93%
“…Our results show that the hemolytic activity of all the compounds was strongly influenced by concentration. Likewise, several authors [18,32,33] have reported similar results for the membrane-lytic activity of the polymers poly(α-ethylacrylic acid) and poly( L -lysine iso-phthalamide), and for arginine-based gemini surfactants, respectively. In the case of polymers, those authors argued that increasing compound concentration enhances the migration of the polymer molecules to lipid bilayer membranes, thereby resulting in an increase in the membrane destabilization.…”
Section: Concentration-dependent Hemolysismentioning
confidence: 52%
“…Their surface tensiometry results were consistent with a micellization process driven by hydrophobic interactions of the polymer and the lipid bilayer. Such a mechanism is similar to that seen for amphiphilic, R-helix-based polypeptides, but the polymer is unlikely to adopt a secondary structure, implying that the hydrophobic-to-hydrophilic ratio is the most important factor in liposome micellization (15). They also found that the rate of micellization was determined by the rate and extent of PEAAc absorption, which in turn was determined by the lateral compressibility of the membrane (16).…”
Section: Discussionmentioning
confidence: 69%
“…We have not investigated the mechanism of this action, but Tirrell and co-workers have studied the disruption of liposomes by PEAAc (15). Their surface tensiometry results were consistent with a micellization process driven by hydrophobic interactions of the polymer and the lipid bilayer.…”
Section: Discussionmentioning
confidence: 92%